Pengaruh Web Pasar Online Keramat Tinggi Terhadap Keputusan Pembelian Masyarakat - Maulana Yusuf; Muhamad Subhan; Aqil Aryansah (JOURNAL SAINS STUDENT RESEARCH, 2023)
This study aims to determine the effect of the online web market on purchasing decisions at the sacred high market, Muara Bulian. The sample used was 96 customers who made repeated purchases through the application or website of the Muara Bulian sacred online market. The sampling technique in this study used a purposive sampling method. Data collection was carried out using a questionnaire with a Likert scale. The analytical method used in this study is a simple regression analysis method with the SPSS 16 application. The results of the research (t test) show that service quality has a significant effect on customer satisfaction with a significance value of 0.000 <0.05. The test results for the Coefficient of Determination obtained RS quare of 0.379. This indicates that the dependent variable is customer satisfaction of 37.9%. influenced by the independent variable of service quality, while 42.1% is influenced by other variables that have not been examined in this study.